The mastery of entrepreneurial project execution in social enterprises in Uganda: a path to sustainable development in rural Africa - Bilgili, Faik; Garang, Aweng Peter Majok; Kassouri, Yacouba; Kuşkaya, Sevda (Springer Nature Singapore, 2026)
Abstract This paper evaluates the feasibility of the proposed East African Monetary Union (EAMU) by examining the effectiveness of monetary transmission mechanisms (MTMs) in the region. This study aims to determine how composite and idiosyncratic shocks propagate within the East Africa Community (EAC) and assess how smaller countries respond to shocks originating from Kenya, the largest economy in the region. We employ panel structural vector autoregression methodology to explore the short- and long-term effects of the dynamics of monetary transmission mechanisms in East African countries (Kenya, Uganda, Tanzania, Rwanda, Burundi, and South Sudan) from 1980 to 2018. Our empirical results prove that in the short run, (i) the contemporaneous response of the interest rate to the output gap shock is positive, (ii) the immediate response of the inflation rate to the output gap shock is negative, and (iii) the response of the inflation rate to the interest rate shock is negative. In the long run, (i) the response of the exchange rate to output gap shock is negative, (ii) the response of the inflation rate to output gap shock is negative, (iii) the response of interest rate to exchange rate shock is positive, (iv) the response of inflation rate to exchange rate shock is negative, and (v) the response of inflation rate to interest rate shock is negative. Overall, these findings shed light on the dynamics of monetary transmission mechanisms in East African countries. The study highlights the short- and long-term effects of various shocks on key macroeconomic variables, such as interest rates, inflation, and exchange rates. These findings have important implications for policymakers, as they seek to stabilize the economy, foster sustainable growth, and fulfill their monetary policy objectives.
Keywords: Entrepreneurial project execution; Social enterprises; Sustainability; Uganda